Assessment of Upper Extremity Function in Multiple Sclerosis: Review and Opinion. Issue 5 (September 2014) - Kraft, George H.; Amtmann, Dagmar; Bennett, Susan E.; Finlayson, Marcia; Sutliff, Matthew H.; Tullman, Mark; Sidovar, Matthew; Rabinowicz, Adrian L.
Abstract : : Upper extremity (UE) dysfunction may be present in up to ˜80% of individuals with multiple sclerosis (MS), although its importance may be under-recognized relative to walking impairment, which is the hallmark symptom of MS. Upper extremity dysfunction affects independence and can impact the ability to use walking aids. Under-recognition of UE dysfunction may result in part from limited availability of performance-based and patient self-report measures that are validated for use in MS and that can be readily incorporated into clinical practice for screening and regularly scheduled assessments. In addition to the 9-Hole Peg Test, which is part of the Multiple Sclerosis Functional Composite, there are several performance-based measures that are generally used in the rehabilitation setting. These measures include the Box and Block Test, the Action Research Arm Test, the Test d'Evaluation de la performance des Membres Supérieurs des Personnes Agées, and the Jebsen-Taylor Test of Hand Function. Several of these measures were developed for use in stroke, although in contrast to stroke, which is characterized by unilateral dysfunction, UE impairment in MS is generally bilateral, and should be assessed as such. Similarly, patient-reported UE measures are available, including Disabilities of the Arm, Shoulder, and Hand (DASH) and its shorter version, QuickDASH, the Manual Ability Measure, and ABILHAND, although none has been psychometrically validated for MS. Recently, item response theory was used to develop a Neuro-QOL (Quality of Life) UE measure and a Patient-Reported Outcomes Measurement Information System UE measure; neither of these have demonstrated sensitivity to change, limiting their use for longitudinal assessment. Consequently, although work is still needed to develop and validate performance-based and patient-reported measures of UE function that are suitable for use in daily MS clinical practice, currently available UE measures can be recommended for incorporation into MS management, albeit with an understanding of their limitations.